Real, compared to what? Insertability of constrained realemes in Dave Eggers’ What is the What (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2021)
The paper examines Eggers’ What is the What (2006) that has problematically been called an autobiographical novel and memoire, narrating Valentino’s chequered past as one of Sudanese Lost Boys. The text yields potential perspectives that demand scrutiny for understanding of the fascinating reciprocity between fictionality and historicity. The article engages theorizations of the complex coalescence offered by Zohar (1980) and McHale (1987) to benchmark the thematic dimensions of the selected text against the cutting-edge postulates. In addition, Valentino’s preface to the “novel”, engaging with the purpose of his collaborative working with Eggers, and Eggers’ essay “It was just boys walking” (2004), negotiating the genesis of the project, have also been used as a methodological touchstone. The analysis vindicates the correspondence between the fictional and the historical versions, albeit the author has fictionalized gaps of Valentino’s historicized life. Thus, Eggers’ text consummates blurring by encompassing both the thematic dimensions, fusing fiction and fact, and the structural schemas, mixing the techniques of different genre traditions, inasmuch as his work exhibits a hermeneutic playfulness found at the heart of the aesthetics of postmodern and 9/11 fiction.